Upaya Mewujudkan Keterwakilan Perempuan di Parlemen dalam Rangka Mendukung Kebijakan Affirmative Action Quota 30 Persen - Sufiarina, Sufiarina (Magister (S2) Ilmu Hukum Fakultas Hukum Universitas Riau, 2018)
This article examines the efforts to realize the policy of women's representation in parliament at least 30%. The study was conducted on a normative juridical with the data provided in various forms of material legal materials. Several articles in Act Number 7 of 2017 on General Election has sought the representation of women in parliament to affirmative action policies 30 percent quota. This policy has been initiated since the election in 2004, but until 2014, the achievement of a minimum 30% quota for women has not been fulfilled. When viewed from the perspective of voters there is the balance between the number of male voters and the number of women voters in the legislative elections, at least on the implementation of the legislative elections in 2014. However, it has not achieved the balance of representation of women and men in parliament. The existence of a balance in the number of male voters and women candidates on election voters list should be an impact on the balance representation of men and women in parliament so that the policy of affirmative action quota of 30% can be realized. Necessary efforts to improve the sensitivity of women in exercising their voting rights and the right to choose either to select an affirmative action policy in order to realize a 30% quota in parliament.